Gestion, évaluation et stabilisation de cuirs archéologiques provenant de la fouille du boulevard Dr Henri-Henrot à Reims/Durocortorum - Céline Bonnot-Diconne (Gallia)
A large volume of waterlogged archaeological leather was discovered in the ZAC du Vieux-Port, on the boulevard Dr. Henri-Henrot, in Reims (Marne). The collection was so impressive that its total and systematic analysis initially had to be delayed. Thus, in June 2010, only 51 inventory numbers, considered to be representative of the whole, had been selected to be considered in priority. After stabilization and study, this first series of selected leathers provided a preview of the general wealth, variety and quality of the remains discovered. This assemblage distinguishes itself from others by the diversity of the models of sandals encountered, their quality of fabrication and the degree of decoration. Luxurious designs were also observed among the closed-toe shoes. The latticework visible on at least four objects is of remarkable quality. The aforementioned observations serve to demonstrate and confirm the significance of the Reims collection: it has provided the opportunity to study a leather object assemblage from a civil urban context, which was non-existent heretofore. Thus, its analysis allowed for the examination of military sites alongside archaeological findings, as well as population types. Only an exhaustive study would be scientifically valid, however, and it would require the prior stabilization of the entire collection. Between 2010 and 2014, the rest of the collection was stored as was, waterlogged, but at room temperature and with rather significant temperature variations within the storage room. Despite the precautionary measures taken, some unfortunate drying and mold growth occurred within the baths. The presence of metal parts had often caused stains on the leather, considerably modifying the appearance of the objects. These oxides had penetrated the leather, altered its mechanical properties and rendered it brittle. Cases of nail adhesion on the film coverings, intended to limit the evaporation of the baths, were also noted. In terms of the condition and conservation of these relics, it was therefore urgent to stabilize, in other words dry, the entire collection. The well-structured supervision and treatment of this material culture, whose manipulation was particularly complex due to its fragile nature, nonetheless allowed for its successful conservation and complete study.